2014
DOI: 10.3109/13668250.2014.965668
|View full text |Cite
|
Sign up to set email alerts
|

Music therapy with young people who have profound intellectual and developmental disability: Four case studies exploring communication and engagement within musical interactions

Abstract: Background The impact of music therapy on the communicative behaviours of young people with profound intellectual and developmental disability has not yet been established. Method Four adolescents participated in individual music therapy (MT) and toy play sessions with the same therapist in a 6-month period. Sessions were video-recorded and analysed based on The Inventory of Potentially Communicative Acts (Sigafoos, J., Arthur-Kelly, M., & Butterfield, N. (2006). Enhancing everyday communication for children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 26 publications
(30 reference statements)
0
54
0
2
Order By: Relevance
“…We did this in order to maximize the impact of the ball in this study for this varying target group. This tailoring to the preferences and capabilities of the user is important for activities for people with profound intellectual disabilities, and has been suggested for visits to multi-sensory rooms [72] and music therapy [248]. The pilot sessions in Chapter 7 also confirmed the advice to adapt to both preferences and capabilities of the participants.…”
Section: Interventionmentioning
confidence: 62%
See 4 more Smart Citations
“…We did this in order to maximize the impact of the ball in this study for this varying target group. This tailoring to the preferences and capabilities of the user is important for activities for people with profound intellectual disabilities, and has been suggested for visits to multi-sensory rooms [72] and music therapy [248]. The pilot sessions in Chapter 7 also confirmed the advice to adapt to both preferences and capabilities of the participants.…”
Section: Interventionmentioning
confidence: 62%
“…We created an interactive ball to address some goals that were set out regarding alertness, shown affect, and amount of movement. I explained the difficulties inherent in doing research with such a user group: doing research on interventions for people with PIMD leads to profound methodological challenges due to the small number of people with homogeneous conditions, fluctuating health differences, contextual differences, and the longer treatment time that is required [248]. I showed that there were large differences in the responses to the ball, three of our nine participants included in the ten sessions showed positive effects on one or more of the targeted measures.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations